Surgical Robotics 2010
DOI: 10.1007/978-1-4419-1126-1_23
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Needle Steering: Design, Modeling, Planning, and Image Guidance

Abstract: This chapter describes how advances in needle design, modeling, planning, and image guidance make it possible to steer flexible needles from outside the body to reach specified anatomical targets not accessible using traditional needle insertion methods. Steering can be achieved using a variety of mechanisms, including tip-based steering, lateral manipulation, and applying forces to the tissue as the needle is inserted. Models of these steering mechanisms can predict needle trajectory based on steering command… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 71 publications
0
97
0
Order By: Relevance
“…A growing body of research has been reported on motion planning for steering needles [23] [24] [25]. The objective is to steer a flexible needle with curvature constraints through tissue to internal targets by exploiting asymmetries at the needle tip.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has been reported on motion planning for steering needles [23] [24] [25]. The objective is to steer a flexible needle with curvature constraints through tissue to internal targets by exploiting asymmetries at the needle tip.…”
Section: Related Workmentioning
confidence: 99%
“…It is also important that channels do not intersect. We build on prior work by Patil et al [24] which uses rapidly exploring random trees (RRT) [28] for planning curvature constrained paths for steerable needles [25].…”
Section: Related Workmentioning
confidence: 99%
“…Robotic needle steering is an emerging technology which utilizes motorized manipulators and medical images to steer a flexible needle tip to reach specified anatomical regions [1,2]. Accurate needle tip placement is a critical issue in robotic needle steering because the performance of the needle-assisted interventions is determined by the amount of deviation between the needle tip and its target [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the motion of the needle is subject to uncertainty due to tissue inhomogeneity, tissue deformation, needle torsion, etc. [7,23]. To address this issue, we follow the suggestion of Kallem [13] that a path with a smaller curvature 0 ≤ κ < κ 0 is small-time locally trackable and that this can be achieved using duty-cycled spinning of the needle during insertion.…”
Section: Introductionmentioning
confidence: 99%